High-pressure structural behavior of α-Fe2O3 studied by single-crystal X-ray diffraction and synchrotron radiation up to 25 GPa - Schouwink, Pascal; Dubrovinsky, Leonid; Glazyrin, Konstantin; Merlini, Marco; Hanfland, Michael; Pippinger, Thomas; Miletich-Pawliczek, Ronald (American mineralogist, 2011)
In situ X‑ray diffraction experiments were carried out at pressures up to 25 GPa on a synthetic hematite (α-Fe 2 O 3 ) crystal using synchrotron radiation in an angle-dispersive setup. Experiments were performed in diamond-anvil cells using neon as a pressure-transmitting medium. Single-crystal diffraction data were collected from omega scans and structural refinements were carried out for 10 pressure points. Bulk and linear incompressibilities were obtained from least-squares fits of refined data to the Eulerian strain based Birch-Murnaghan equation of state. Finite strain analysis suggests a truncation at second order, yielding results of K 0 = 207(3), Ka 0 = 751(17), and K c0 = 492(8) for bulk and axial moduli, respectively. The a-axis is about 1.5 times stiffer than the c-axis. Compression of the main structural feature, the FeO 6 octahedra, is quite uniform, with just slight changes of distortion parameters at higher pressures.
Im Titel sind die Ziffern 2 und 3 bei α-Fe2O3 jeweils tiefgestellt
Elektronische Reproduktion der Druckausgabe
Gesehen am 26.10.2022